Developing a 160 kW continuous wave circulator for the P-band high-frequency system of the Wuhan light source - XIAO Chengcheng; ZHANG Qiang; WANG Cheng; ZHANG Junqiang; FANG Wencheng; XU Yiming (He jishu)
BackgroundSolid-state amplifiers of synchrotron radiation high-frequency cavity equipment may sustain unrecoverable damage due to the excessive reflected power resulting from load detuning, a high-power circulator is used to guide the reflected power to the absorbing load and thus protect the power source. In this case, if the reflected power suddenly increases during device operation, the temperature of the circulator cavity will be risen and the parameter characteristics of the gyromagnetic ferrite will be changed in the circulator, and eventually lead to poor absorption of the reflected power by the load.PurposeThis study aims to design and develop a circulator with a temperature compensation control unit, capable of functioning at 499.654 MHz with a 160 kW continuous wave radiofrequency power.MethodsFirstly, the circulator was simulated and optimized using the HFSS software. Thermal simulation shows that the temperature rise of ferrite sheets under 160 kW continuous wave is less than 13 °C. Then, impedance matching was performed on the circulator using tuners arranged at each of the three ports, and feedforward control was used to compensate for the temperature changes. Finally, a constant temperature water tank was employed to simulate the change in water temperature during actual operation, the reliability of temperature compensation function of the control unit was verified by the performance of the circulator restoring to the best condition.ResultsThe insertion loss is better than -29 dB under the worst case of a complete short circuit at the output port, the circulator loss is less than 0.1 dB in the bandwidth of ±5 MHz, and this loss reaches 0.06 dB at the center frequency.ConclusionsThe S parameters of the circulator meet the design requirements, and the reliability of the temperature control compensation unit of circulator is verified by constant temperature water tank simulation test in this study.